Study on enhancement programmes conducted by Malaysian Islamic financial institutions - Othman, Ahmad Azam; Hassan, Rusni; Omar, Muhammad Naim; Mohd Napiah, Mohammad Deen; Arifin, Mahamad (2013)
The Central Bank of Malaysia (Central Bank) has introduced and issued the Shariah Governance Framework for Islamic Financial Operators (IFIs) 2010 (SGF 2010) in October 2010 to all IFIs under the Central Bank jurisdictions to have a proper Shariah governance that need to be adopted accordingly. The IFIs need to confirm that they have met all the requirements and are operating in accordance with it. One of the primary objectives of SGF 2010 is to enhance the role of the Board of Directors (Board), Shariah Committee (SC) and the management in relation to Shariah matters, including enhancing the relevant key organs having the responsibility to execute the Shariah compliance and research functions aimed at the attainment of a Shariah based operating environment. Thus, this study investigates the enhancement programmes organized and participated by relevant key organs of the IFIs. It analyses the budget allocation for the enhancement programmes, types of enhancement programmes and the enhancement programmes target group respectively. This is done through the collection of data and information by distributing the questionnaire to the respondents who involved in IFIs’ industries such as the management of the IFIs, be it Islamic banks and Takaful operators, management of the IFIs, SC and Shariah officers. Most of the data in this study were collected and analyzed using the Statistical Package for Social Sciences (SPSS) software version 16.0 and Microsoft Excel. Additional the descriptive analysis is used to determine the number of frequencies and percentages. The findings and analysis show that the IFIs have adopted the objective of the SGF 2010 accordingly by setting aside certain amount of monies for enhancement programmes for certain targeted groups who are the participants of the programmes.